Sodometries - Goldberg, Jonathan (Fordham University Press, 2010)
'Sodometries' has decisively shaped work in the history of sexuality for the last decade and remains a critical text for this developing field ... Goldberg's work is already a classic and has not been superseded.
10.5422/fordham/9780823232215.001.0001
Keywords: Literatur; Englisch; Homosexualität; Homophobie; English literature; Sodomy in literature; Male homosexuality in literature; Sexual orientation in literature; Sodomy; Homosexuality; Homophobia